[Brief on Bill 86 Presented to the Parliamentary Committee of Culture and Education] - English Parents' Committee Association (EPCA) (2016)

Projet 294 : Perspectives from Parents on the Overhaul of the Funding and Organization of Services for Handicapped Students and Students With Social Maladjustments or Learning Difficulties - English Parents' Committee Association (EPCA) (2021)

[English Parents’ Committee Association Exclusion by the Government of Quebec for the Parliamentary Committee Hearings on Bill 23] - English Parents' Committee Association (EPCA) (2023)

A Public Consultation Brief on Bill 47 : An Act to Reinforce the Protection of Students - English Parents' Committee Association (EPCA) (2024)
With this brief, EPCA argues that solutions must be put in place that go further to protect students in their learning environments and that put in the forefront their physical and psychological wellbeing. These recommendations are imperatives born of the urgent need to correct existing deficiencies and usher in an era where our educational institutions are safe and nurturing for every child.

Newsletter - English Parents' Committee Association (EPCA) (2022)
Number of pages: 11